Two Plays: Stolen Seed and Refugees of the Great Lakes (2018)
Refugees of the Great Lakes is a play passionately conceived upon the realities of the experience of the refugees of the Great Lakes of Central Africa after the mass genocide of the Hutus and Tutsis in Rwanda in 1994. The work centres on the nightmarish post war experience of the victims of war. It portrays the harsh realities of being refugees on the women and children, particularly the child-soldiers who were declared wanted in Kigali because of their involvement in the carnage. Refugees of the Great Lakes is set in Kibumba and some of the Central Africa refugee camps such as Katale, Tshondo and Mugunga. It is heart rending that some of the refugees remained in these camps for years and in spite of their initial experience and circumstance continue to suffer contentions, disunity and conflicts that typically generate war. The recurring imagery of wasted years, the hopelessness of war, the psychological and catastrophic consequences of war, the state of inertia, the senseless tragedies — particularly the reality and the shock of the deaths of the refugees in the camps from the ravages of epidemics — paint a clear picture of the compelling horrors of war and its aftermath. The premiere of the play on the 23rd of April, 2014 in Olabisi Onabanjo University, O gun State, Nigeria, coincided with the activities that began on the 6th of April, 2014 held to commemorate 20 years of the Rwandan genocide in Rwanda. The nation commenced a week of official mourning to mark the country’s painful history; a period of reminiscing and remembrance of the heroes, the villains and the innocent. What is perhaps most instructive is that several nations have come to the brink of war or have gone to war despite the fact that instances of the irreparable consequences of A'ar abound. This play queries all the great wars ever fought in Africa and in the entire world. The characters portrayed here are honour of all the victims; the great men, women and children who braced the wars and the invincible peace pacts signed by the women of war.